Conversational Maxim Violation by the Main Character in the Shang-Chi and the Legend of the Ten Rings Movie - Putu Ameylia Maheswari Dewi; Ni Nyoman Deni Ariyaningsih (Lexicon, 2023)
This study aims to identify the types of conversational maxims violation that the violated by the main character found in the Shang-Chi and the Legend of the Ten Rings Movie. Conversational maxim is a set of rule proposed by Grice (1975) that categorizes into four types, which are maxim of quantity, quality, relation, and manner. These rules are important to make an effective and clear conversation. By violating maxims, the participants of the conversation broke the rules of cooperative principle. The participants of the conversation seem to hide the real intended meanings and certain purposes which are conveyed by the speaker behind the utterance. This research uses theory by Grice’s Cooperative Principle and also support with theory by Cutting to analyze four types of conversational maxims violation. The method used to conduct this research is descriptive qualitative method. The amount of maxim violation of quantity is 6 (40%), that appears most frequently throughout the film. The violation of maxim of quality becomes the second violation that frequently found, that brings the total 4 violations (26,6%), also the third violation that occurs is violations of maxim of relation with 3 violations in total (20%). The main character violates the maxim of manners 2 times in totals (13,4%) more than any other violation, which is the least common infraction in the film.